Mothers’ Knowledge of Infant Health and Nutritional Status: A Case Study - Sybil, Amirah (Medical Technology and Public Health Journal, 2025)
The increasing incidence of stunting in Indonesia is concerning, highlighting the urgent need to reduce its prevalence. This study evaluated maternal knowledge regarding eating and parenting habits and the nutritional status of infants aged 0-59 months. Conducted in March 2024 at the Posyandu RW 07 in Wonokromo Village, Surabaya City, the study involved a sample size of 97 out of a total population of 145. This descriptive study employed a survey approach, targeting mothers attending the Posyandu in RW 07. The results indicated that the nutritional status of toddlers aged 0-59 months was generally within a healthy range. Mothers also demonstrated a commendable level of knowledge in child-rearing and food provision. Based on weight-for-age measurements, 75 infants were classified as having a normal nutritional status, consisting of 45 males and 30 females, representing 77.32% of the sample. Similarly, height-for-age assessments showed that 77 infants fell into the normal range, with 49 males and 28 females, accounting for 79.38%. Furthermore, maternal knowledge regarding feeding habits in RW 07 was notably high, with 100% of mothers exhibiting good feeding practices. Likewise, 100% of mothers demonstrated sound parenting practices, indicating that all mothers in this study have implemented effective parenting habits Keywords: Balanced nutrition, Eating Patterns, Growth and Development, Parenting Patterns